Organic electroluminescent element
By incorporating a coating layer of organic and/or inorganic materials between the substrate and electrode, the device's atmospheric stability is improved, addressing pinhole formation and moisture issues, resulting in enhanced durability.
Patent Information
- Application Number
- JP2023101614
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
Organic electroluminescent devices suffer from low atmospheric stability due to the difficulty in completely removing impurities from the substrate, leading to pinhole formation in the electrode layer and reduced durability, which is exacerbated by moisture absorption.
A coating layer of organic and/or inorganic materials with a thickness of 210 nm to 30 μm is applied adjacent to the substrate, which flattens the surface and reduces pinhole formation, improving atmospheric stability by minimizing moisture absorption and enhancing thermophysical properties.
The proposed structure significantly enhances the atmospheric stability of organic electroluminescent devices, maintaining performance even in harsh environments with high humidity, thereby extending their lifespan.
Smart Images

Figure 2025001877000002 
Figure 2025001877000003 
Figure 2025001877000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic electroluminescent device, and more particularly to an organic electroluminescent device that can be used as a display device such as a display unit of an electronic device, a lighting device, or the like. [Background technology]
[0002] Organic electroluminescent devices (organic EL devices) are expected to be new light-emitting devices that can be used in display devices and lighting. An organic electroluminescent device has a structure in which one or more layers, including a light-emitting layer formed by containing a light-emitting organic compound, are sandwiched between an anode and a cathode, and emits light by exciting the light-emitting organic compound using the energy generated when holes injected from the anode and electrons injected from the cathode recombine. Organic electroluminescent devices are current-driven devices, and various studies have been conducted on the device structure and materials of the layers that make up the device in order to utilize the flowing current more efficiently.
[0003] The most basic and widely studied structure of organic electroluminescent devices is the three-layer structure proposed by Adachi et al. (see Non-Patent Document 1), which has a hole transport layer, light-emitting layer, and electron transport layer sandwiched in that order between an anode and a cathode. Since this proposal, organic electroluminescent devices have been based on a three-layer structure, and numerous studies have been conducted to improve performance such as efficiency and lifespan by dividing up the roles. The basis of this idea is that the injected electrons have high energy (in the electrode) at that point. Therefore, organic electroluminescent devices are generally prone to degradation by oxygen and water, and strict sealing is essential to prevent their intrusion. The causes of degradation include the fact that the materials that can be used as the cathode are limited to those with small work functions, such as alkali metals and alkali metal compounds, due to the ease of electron injection into organic compounds, and that the organic compounds themselves used are prone to react with oxygen and water. The strict sealing gives organic electroluminescent devices an advantage over other light-emitting devices, but at the same time it sacrifices their advantages, such as low cost and flexibility. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] "Japanese Journal of Applied Physics", 1988, Vol. 27, L269 Summary of the Invention [Problem to be solved by the invention]
[0005] Generally, organic electroluminescent devices are tightly sealed, which sacrifices features such as low cost and flexibility. In order to advance the application of organic electroluminescent devices to fields where future development is expected, such as wearable devices, it is necessary to further improve the atmospheric stability of organic electroluminescent devices so that they can be used without strict sealing in order to improve their flexibility.
[0006] The present invention has been made in view of the above-mentioned circumstances, and has an object to provide an organic electroluminescent device having improved stability in the atmosphere. [Means for solving the problem]
[0007] The present inventors have conducted various studies on methods for improving the atmospheric stability of organic electroluminescent devices, and have found that it is difficult to completely remove impurities adhering to the substrate, and that forming a lower electrode directly on a substrate having such impurities adhering thereto by vapor deposition generates pinholes in the electrode layer, which causes a decrease in the atmospheric stability of the device. The inventors have then found that the atmospheric stability of the device can be improved by forming a coating layer of an organic material and / or an inorganic material having a thickness of 210 nm to 30 μm on the substrate, and have arrived at the present invention.
[0008] That is, the present invention is as follows. [1] An organic electroluminescent device having a structure in which one of an anode and a cathode is a lower electrode and the other is an upper electrode, and a plurality of layers are laminated between the lower electrode and the upper electrode, The organic electroluminescent device is characterized by having, in this order, a substrate, a coating layer of an organic material and / or an inorganic material having a thickness of 210 nm to 30 μm formed adjacent to the substrate, a lower electrode, an organic compound layer, and an upper electrode.
[0009] [2] The organic electroluminescent device according to [1], wherein the coating layer is a coating layer made of an organic material.
[0010] [3] The organic electroluminescent device according to [2], wherein the organic material has a glass transition temperature higher than that of the substrate.
[0011] [4] The organic electroluminescent device according to any one of [1] to [3], wherein the lower electrode is a cathode and the upper electrode is an anode.
[0012] [5] The organic electroluminescent device according to any one of [1] to [4], further comprising an oxide layer between the coating layer and a lower electrode.
[0013] [6] A display device comprising the organic electroluminescent device according to any one of [1] to [5].
[0014] [7] A lighting device comprising the organic electroluminescent device according to any one of [1] to [5]. Effect of the Invention
[0015] The organic electroluminescent device of the present invention has the above-mentioned configuration, and is an organic electroluminescent device having improved atmospheric stability by providing a coating layer of an organic material and / or an inorganic material of a predetermined thickness between the substrate and the lower electrode. [Brief description of the drawings]
[0016] [Figure 1] 1 is a diagram showing a laminate structure of an organic electroluminescent device 1 produced in Example 1. FIG. [Diagram 2] FIG. 2 is a diagram showing the EL emission state of the organic electroluminescent device 1 produced in Example 1 after it was left for 100 hours in an environment of relative humidity of 85%. [Diagram 3] FIG. 2 is a diagram showing the EL emission state of the organic electroluminescent device 1 produced in Example 2 after being left in an environment of relative humidity of 85% for 100 hours. [Figure 4] FIG. 13 is a diagram showing the EL emission state of the organic electroluminescent device 1 produced in Example 3 after being left for 100 hours in an environment of relative humidity of 85%. [Diagram 5] FIG. 2 is a diagram showing the EL emission state of the organic electroluminescent device 1 produced in Comparative Example 1 after being left in an environment of relative humidity of 85% for 100 hours. [Figure 6] FIG. 13 is a diagram showing the EL emission state of the organic electroluminescent device 1 produced in Comparative Example 2 after being left in an environment of relative humidity of 85% for 100 hours. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.
[0018] The organic electroluminescent device of the present invention is characterized by having a coating layer of an organic material and / or an inorganic material having a thickness of 210 nm to 30 μm formed adjacent to a substrate, and having a lower electrode on the coating layer. As the substrate for an organic electroluminescent device, a substrate formed of polyethylene terephthalate, polyethylene naphthalate, cycloolefin polymer, etc. and having a barrier layer for sealing thereon is usually used. In such a substrate, it is inevitable that fine impurities will adhere to the barrier layer surface, and once the impurities adhere, it is extremely difficult to completely remove the impurities from the surface of the barrier layer, which is a resin layer. If a lower electrode is formed directly on a substrate having such impurities adhered thereto by deposition, pinholes will occur in the electrode layer, which will cause a decrease in the atmospheric stability of the device. In contrast, by forming a coating layer of an organic material and / or an inorganic material having a thickness of 210 nm or more on the substrate, the surface on which the lower electrode is to be formed can be flattened, and by forming the lower electrode on such a flattened surface, the occurrence of pinholes in the electrode layer can be suppressed. On the other hand, the coating layer may absorb moisture, which is a factor in reducing the life of the device. The present inventors have conducted various studies on these issues and have found that by setting the thickness of the coating layer to 210 nm to 30 μm, it is possible to suppress the occurrence of pinholes in the electrode layer while suppressing the effect of moisture absorption of the coating layer, and to improve the atmospheric stability of the device. Furthermore, as described below, when a coating layer of such a thickness is formed using an organic material having a higher glass transition temperature than the substrate as the material for the coating layer, it is possible to obtain the effect of improving the thermal properties of the substrate while suppressing the influence of moisture absorption by the coating layer.
[0019] The coating layer formed adjacent to the substrate may be one layer or two or more layers. When it is two or more layers, the total thickness of all layers may be 210 nm to 30 μm. The thickness of the coating layer may be from 210 nm to 30 μm, preferably from 300 nm to 20 μm, and more preferably from 500 nm to 5 μm. The thickness of the coating layer can be measured by a stylus type step gauge.
[0020] The coating layer formed adjacent to the substrate is formed of organic and / or inorganic materials. Examples of organic materials include epoxy resins, polyimide resins, acrylic resins, methacrylic resins, polystyrene resins, aminoalkyd resins, urethane resins, silicone resins, fluororesins, melamine resins, polyester resins, etc., and one or more of these can be used. Among these, photocurable resins that can be cured at low temperatures and in a short time are preferred, and photocurable epoxy resins and photocurable acrylic resins are preferred. Examples of inorganic materials include organic metal salt solutions such as magnesium acetylacetonate, zinc acetylacetonate, zinc acetate, magnesium acetate, calcium acetate, and aluminum acetate; and zinc oxide, titanium oxide, silicon oxide, aluminum oxide, indium tin oxide, antimony tin oxide, zirconium oxide, and magnesium oxide formed by a sol-gel method. One or more of these can be used, and a mixture with an organic substance can also be used.
[0021] The coating layer may be a coating layer of an organic material, a coating layer of an inorganic material, or a coating layer using both of these, but is preferably a coating layer of an organic material. When an organic material is used, it is easy to form a coating layer with a relatively large thickness, and it is possible to form a coating layer with a flat surface that more sufficiently eliminates the influence of impurities on the substrate.
[0022] The organic material preferably has a glass transition temperature (Tg) higher than that of the substrate. By forming a coating layer having a thickness of 210 nm or more on the substrate using an organic material having a glass transition temperature higher than that of the substrate, the coating layer can compensate for the thermal properties of the substrate even when a substrate having a low Tg is used, and the thermal properties of the substrate can be improved. Such an effect of improving the thermal properties of the substrate can be obtained if the organic material has a higher Tg than the substrate, but the organic material preferably has a Tg that is 5° C. or more higher than the substrate, more preferably has a Tg that is 10° C. or more higher than the substrate, and even more preferably has a Tg that is 20° C. or more higher than the substrate. The Tg of the organic material is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher. In order to obtain the effect of improving the thermal properties of the substrate, the film formed from the organic material does not necessarily have to be a coating film. Therefore, when the only purpose is to improve the thermal properties of the substrate, the film formed adjacent to the substrate does not necessarily have to be formed by coating, and may be a film formed by other methods such as vapor deposition. The glass transition temperature of the organic material can be measured by a differential thermal analyzer.
[0023] The organic electroluminescent device of the present invention may have a lower electrode formed adjacent to the coating layer, or another layer may be formed between the coating layer and the lower electrode. The other layer may be an oxide layer, and having an oxide layer between the coating layer and the lower electrode is one of the preferred embodiments of the organic electroluminescent device of the present invention. By forming an oxide layer between the coating layer and the lower electrode, the adhesion of the lower electrode can be improved compared to when the lower electrode is formed directly on the coating layer by vapor deposition.
[0024] Examples of oxides that form the oxide layer include zinc oxide, titanium oxide, silicon oxide, aluminum oxide, indium tin oxide, antimony tin oxide, zirconium oxide, magnesium oxide, molybdenum oxide, indium-doped zinc oxide, and fluorine-doped indium oxide, and one or more of these can be used.
[0025] The thickness of the oxide layer is not particularly limited, but is preferably 1 to 1000 nm, more preferably 5 to 500 nm, and further preferably 10 to 100 nm. The thickness of the oxide layer can be measured by a stylus step gauge.
[0026] The structure between the lower electrode and the upper electrode of the organic electroluminescent device of the present invention will be described below. The structure of the organic electroluminescence device of the present invention is not particularly limited, but it is preferable that the device has a cathode, an electron injection layer and / or an electron transport layer, a light emitting layer, a hole transport layer and / or a hole injection layer, and an anode, adjacent to each other in this order. Each of these layers may consist of one layer or two or more layers. In the organic electric field element having the above-mentioned configuration, when the element has only one of the electron injection layer and the electron transport layer, the one layer is laminated adjacent to the cathode and the light-emitting layer, and when the element has both the electron injection layer and the electron transport layer, these layers are laminated adjacent to the cathode, the electron injection layer, the electron transport layer, and the light-emitting layer in this order. When the element has only one of the hole transport layer and the hole injection layer, the one layer is laminated adjacent to the light-emitting layer and the anode, and when the element has both the hole transport layer and the hole injection layer, these layers are laminated adjacent to the light-emitting layer, the hole transport layer, the hole injection layer, and the anode in this order.
[0027] The organic electroluminescent device may be a forward structure device in which the lower electrode is an anode and the upper electrode is a cathode, or may be an inverted structure device in which the lower electrode is a cathode and the upper electrode is an anode, but since an inverted structure device has higher atmospheric stability than an inverted structure device, the organic electroluminescent device of the present invention is preferably an inverted structure device, which can provide the organic electroluminescent device of the present invention with higher atmospheric stability.
[0028] The organic electroluminescence element of the present invention is preferably an organic-inorganic hybrid type organic electroluminescence element further having a metal oxide layer between the cathode and the anode. By using a metal oxide as a material for the element, the organic electroluminescence element can have higher resistance to water vapor. The organic electroluminescent device of the present invention is an organic-inorganic hybrid type organic electroluminescent device having a metal oxide layer between an anode and a cathode, and is preferably an element having a configuration in which an electron injection layer and, if necessary, an electron transport layer are between the cathode and the light-emitting layer, and a hole transport layer and / or a hole injection layer are between the anode and the light-emitting layer. The organic electroluminescent device of the present invention may have other layers between these layers, but is preferably an element consisting of only these layers. That is, it is preferable that the element is an element in which the layers of the cathode, the electron injection layer, if necessary, the electron transport layer, the light-emitting layer, the hole transport layer and / or the hole injection layer, and the anode are laminated adjacent to each other in this order. Each of these layers may be composed of one layer, or may be composed of two or more layers.
[0029] In the organic electroluminescent device of the present invention, as the material for forming the light-emitting layer, any compound that can be usually used as a material for a light-emitting layer can be used. The compound may be a low molecular weight compound or a high molecular weight compound, or these may be used in combination. In the present invention, a low molecular weight material means a material that is not a high molecular weight material (polymer), and does not necessarily mean an organic compound having a low molecular weight.
[0030] Examples of the polymeric material for forming the light-emitting layer include polyacetylene compounds such as trans-polyacetylene, cis-polyacetylene, poly(diphenylacetylene) (PDPA), and poly(alkyl, phenylacetylene) (PAPA); poly(para-phenylenevinylene) (PPV), poly(2,5-dialkoxy-para-phenylenevinylene) (RO-PPV), cyano-substituted-poly(para-phenylenevinylene) (CN-PPV), poly Polyparaphenylenevinylene compounds such as (2-dimethyloctylsilyl-paraphenylenevinylene) (DMOS-PPV) and poly(2-methoxy,5-(2'-ethylhexoxy)-paraphenylenevinylene) (MEH-PPV); polythiophene compounds such as poly(3-alkylthiophene) (PAT) and poly(oxypropylene)triol (POPT); poly(9,9-dialkylfluorene) (PDAF) and poly(dioctylfluorene) (PDAF); Polyfluorene compounds such as α,ω-bis[N,N'-di(methylphenyl)aminophenyl]-poly[9,9-bis(2-ethylhexyl)fluorene-2,7-diyl] (PF2 / 6am4), poly(9,9-dioctyl-2,7-divinylenefluorenyl-ortho-co(anthracene-9,10-diyl); poly(para-phenylene) (PPP), poly(1,5-dialkoxy-pa Examples of suitable polymeric materials include polyparaphenylene-based compounds such as poly(para-phenylene) (RO-PPP); polycarbazole-based compounds such as poly(N-vinylcarbazole) (PVK); polysilane-based compounds such as poly(methylphenylsilane) (PMPS), poly(naphthylphenylsilane) (PNPS), and poly(biphenylylphenylsilane) (PBPS); and boron compound-based polymeric materials described in Japanese Patent Application No. 2010-230995 and Japanese Patent Application No. 2011-6457.
[0031] Examples of low molecular weight materials for forming the light emitting layer include a three-coordinate iridium complex having 2,2'-bipyridine-4,4'-dicarboxylic acid as a ligand, factolis(2-phenylpyridine)iridium (Ir(ppy)3), 8-hydroxyquinoline aluminum (Alq3), tris(4-methyl-8-quinolinolato)aluminum(III) (Almq3), 8-hydroxyquinoline zinc (Znq2), (1,10-phenanthroline)-tris-(4,4,4-trifluoro-1-(2-thienyl)-butane-1,3-dionate)europium(III) (Eu(TTA)3(phen)), and 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine. Various metal complexes such as platinum(II); benzene-based compounds such as distyrylbenzene (DSB) and diaminodistyrylbenzene (DADSB); naphthalene-based compounds such as naphthalene and Nile Red; phenanthrene-based compounds such as phenanthrene; chrysene-based compounds such as chrysene and 6-nitrochrysene; perylene-based compounds such as perylene and N,N'-bis(2,5-di-t-butylphenyl)-3,4,9,10-perylene-di-carboximide (BPPC); coronene-based compounds such as coronene; anthracene-based compounds such as anthracene and bisstyrylanthracene; pyrene-based compounds such as pyrene; 4-(di-cyanomethylene)-2-methyl-6-(para-dimethylaminostyryl)-4H-pyran (DC pyran compounds such as M); acridine compounds such as acridine; stilbene compounds such as stilbene; thiophene compounds such as 2,5-dibenzoxazolethiophene; benzoxazole compounds such as benzoxazole; benzimidazole compounds such as benzimidazole; benzothiazole compounds such as 2,2'-(para-phenylenedivinylene)-bisbenzothiazole; butadiene compounds such as bistyryl(1,4-diphenyl-1,3-butadiene), tetraphenylbutadiene; naphthalimide compounds such as naphthalimide; coumarin compounds such as coumarin; perinone compounds such as perinone; oxadiazole compounds such as oxadiazole; aldazine compounds;Examples of suitable materials include cyclopentadiene compounds such as 1,2,3,4,5-pentaphenyl-1,3-cyclopentadiene (PPCP); quinacridone compounds such as quinacridone and quinacridone red; pyridine compounds such as pyrrolopyridine and thiadiazolopyridine; spiro compounds such as 2,2',7,7'-tetraphenyl-9,9'-spirobifluorene; metal or metal-free phthalocyanine compounds such as phthalocyanine (H2Pc) and copper phthalocyanine; and boron compound materials described in JP-A-2009-155325, JP-A-2010-230995, and JP-A-2011-6458. In addition, products of Chemipro Chemicals such as KHLHS-04 and KHLDR-03 can also be used.
[0032] The average thickness of the light-emitting layer is not particularly limited, but is preferably from 10 to 150 nm, more preferably from 20 to 100 nm, and even more preferably from 40 to 100 nm. The average thickness of the light-emitting layer can be measured by a quartz crystal film thickness gauge in the case of a low molecular weight compound, and by a contact step gauge in the case of a high molecular weight compound.
[0033] When the organic electroluminescent device of the present invention has an electron transport layer, the material thereof may be any compound that can be usually used as a material for an electron transport layer, and these may be used in combination. Examples of compounds that can be used as materials for the electron transport layer include pyridine derivatives such as tris-1,3,5-(3'-(pyridin-3''-yl)phenyl)benzene (TmPyPhB), quinoline derivatives such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ)), pyrimidine derivatives such as 2-phenyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine (BPyPPM), pyrazine derivatives, phenanthroline derivatives such as bathophenanthroline (BPhen), triazine derivatives such as 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)-4-biphenyl)-[1,3,5]triazine (MPT), triazole derivatives such as 3-phenyl-4-(1'-naphthyl)-5-phenyl-1,2,4-triazole (TAZ), and oxazole derivatives. oxadiazole derivatives such as 2-(4-biphenylyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD); imidazole derivatives such as 2,2',2''-(1,3,5-benzenetriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBI); aromatic ring tetracarboxylic acid anhydrides such as naphthalene and perylene; various metal complexes such as bis[2-(2-hydroxyphenyl)benzothiazolato]zinc (Zn(BTZ)2) and tris(8-hydroxyquinolinato)aluminum (Alq3); and organic silane derivatives such as silole derivatives such as 2,5-bis(6'-(2',2''-bipyridyl))-1,1-dimethyl-3,4-diphenylsilole (PyPySPyPy). One or more of these can be used. Among these, metal complexes such as Alq3 and pyridine derivatives such as TmPyPhB are preferred.
[0034] As the electron injection layer, a layer made of a nitrogen-containing film formed from a nitrogen-containing compound can be used. Examples of the nitrogen-containing compound that forms the layer made of the nitrogen-containing film include pyrrolidones such as polyvinylpyrrolidone, pyrroles such as polypyrrole, anilines such as polyaniline, and pyridines such as polyvinylpyridine, as well as compounds having a nitrogen-containing heterocycle such as pyrrolidines, imidazoles, piperidines, pyrimidines, and triazines, and amine compounds.
[0035] The nitrogen-containing compound is preferably a compound with a high nitrogen content, and is preferably a polyamine, which has a high ratio of the number of nitrogen atoms to the total number of atoms constituting the compound, and is therefore suitable for providing an organic electroluminescent device with high electron injection properties and driving stability. The polyamines are preferably those capable of forming a layer by coating, and may be low molecular weight compounds or high molecular weight compounds. As low molecular weight compounds, polyalkylene polyamines such as diethylenetriamine and pentamethyldiethylenetriamine are preferably used, and as high molecular weight compounds, polymers having a polyalkyleneimine structure are preferably used. In particular, polyethyleneimine is preferred. Among them, one of the preferred embodiments of the present invention is that the nitrogen-containing compound is polyethyleneimine or diethylenetriamine. Here, a low molecular weight compound means a compound that is not a high molecular weight compound (polymer), and does not necessarily mean a compound with a low molecular weight.
[0036] The average thickness of the nitrogen-containing film is not particularly limited, but is preferably 0.5 to 10 nm, more preferably 1 to 5 nm, and further preferably 1 to 3 nm. The average thickness of the electron injection layer can be measured by a quartz crystal film thickness meter in the case of a low molecular weight compound.
[0037] When the organic electroluminescent device of the present invention has a hole transport layer, the hole transporting organic material used for the hole transport layer may be any of various p-type polymeric materials and various p-type low molecular weight materials, either alone or in combination. Examples of p-type polymeric materials (organic polymers) include polyarylamines, fluorene-arylamine copolymers, fluorene-bithiophene copolymers, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophenes, polyhexylthiophene, poly(p-phenylenevinylene), polytinylenevinylene, pyrene formaldehyde resins, ethylcarbazole formaldehyde resins, or derivatives thereof. These compounds can also be used in mixtures with other compounds, such as polythiophene-containing mixtures such as poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS).
[0038] Examples of the p-type low molecular weight material include arylcycloalkane compounds such as 1,1-bis(4-di-para-triaminophenyl)cyclohexane and 1,1'-bis(4-di-para-tolylaminophenyl)-4-phenyl-cyclohexane, 4,4',4''-trimethyltriphenylamine, N,N,N',N'-tetraphenyl-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD1), N,N'-diphenyl-N,N'-bis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N,N',N'-tetrakis(4-methoxyphenyl) arylamine compounds such as N,N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), TPTE; phenylenediamine compounds such as N,N,N',N'-tetraphenyl-p-phenylenediamine, N,N,N',N'-tetra(p-tolyl)-p-phenylenediamine, N,N,N',N'-tetra(meta-tolyl)-meta-phenylenediamine (PDA); carbazole compounds such as carbazole, N-isopropylcarbazole, and N-phenylcarbazole; stilbene compounds such as 4-di-p-tolylaminostilbene; xZ, triphenylmethane, triphenylmethane compounds such as m-MTDATA, pyrazoline compounds such as 1-phenyl-3-(para-dimethylaminophenyl)pyrazoline, benzine (cyclohexadiene) compounds, triazole compounds such as triazole, imidazole compounds such as imidazole, oxadiazole compounds such as 1,3,4-oxadiazole, 2,5-di(4-dimethylaminophenyl)-1,3,4-oxadiazole, anthracene compounds such as 9-(4-diethylaminostyryl)anthracene, fluorenone compounds such as 2,4,7-trinitro-9-fluorenone, 2,7-bis(2-hydroxy-3-(2-chlorophenylcarbamoyl)-1-naphthylazo)fluorenone, polya Examples of the compound include aniline-based compounds such as aniline, silane-based compounds, pyrrole-based compounds such as 1,4-dithioketo-3,6-diphenyl-pyrrolo-(3,4-c)pyrrolopyrrole, florene-based compounds such as florene, porphyrin-based compounds such as porphyrin and metal tetraphenylporphyrin, quinacridone-based compounds such as quinacridone, metallic or non-metallic phthalocyanine-based compounds such as phthalocyanine, copper phthalocyanine, tetra(t-butyl)copper phthalocyanine, and iron phthalocyanine, metallic or non-metallic naphthalocyanine-based compounds such as copper naphthalocyanine, vanadyl naphthalocyanine, and monochlorogallium naphthalocyanine, and benzidine-based compounds such as N,N'-di(naphthalene-1-yl)-N,N'-diphenyl-benzidine and N,N,N',N'-tetraphenylbenzidine.
[0039] When the organic electroluminescent device of the present invention has an electron transport layer or a hole transport layer, the average thickness of these layers is not particularly limited, but is preferably 5 to 200 nm, more preferably 10 to 100 nm, and further preferably 15 to 50 nm. The average thickness of the electron transport layer or hole transport layer can be measured by a quartz crystal film thickness meter in the case of a low molecular weight compound, and by a contact step gauge in the case of a high molecular weight compound.
[0040] When the organic electroluminescent element of the present invention has a metal oxide layer, the metal oxide layer is provided between the cathode and the light-emitting layer, between the anode and the light-emitting layer, or both. However, it is preferable to have a metal oxide layer between the cathode and the light-emitting layer and between the light-emitting layer and the anode. If the metal oxide layer between the cathode and the light-emitting layer is the first metal oxide layer and the metal oxide layer between the anode and the light-emitting layer is the second metal oxide layer, it is preferable that the first metal oxide layer is used as an electron injection layer and the second metal oxide layer is used as a hole injection layer. An example of a preferred element configuration of the organic electroluminescent element of the present invention is a configuration in which a cathode, a first metal oxide layer, a layer made of a nitrogen-containing film, a light-emitting layer, a hole transport layer, a second metal oxide layer, and an anode are laminated adjacent to each other in this order. Note that an electron transport layer may be provided between the layer made of a nitrogen-containing film and the light-emitting layer as necessary. The importance of the metal oxide layer is higher for the first metal oxide layer, and the second metal oxide layer can be replaced by an organic material with an extremely deep lowest unoccupied molecular orbital, such as HATCN.
[0041] The first metal oxide layer is a layer consisting of a single metal oxide film, or a semiconductor or insulator laminated thin film layer which is a layer consisting of a single metal oxide film or a laminated and / or mixed layer of two or more metal oxides. The metal elements constituting the metal oxide are selected from the group consisting of magnesium, calcium, strontium, barium, titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, indium, gallium, iron, cobalt, nickel, copper, zinc, cadmium, aluminum, and silicon. Of these, it is preferable that at least one of the metal elements constituting the laminated or mixed metal oxide layer is a layer consisting of magnesium, aluminum, calcium, zirconium, hafnium, silicon, titanium, or zinc, and among them, it is preferable that the single metal oxide contains a metal oxide selected from the group consisting of magnesium oxide, aluminum oxide, zirconium oxide, hafnium oxide, silicon oxide, titanium oxide, and zinc oxide.
[0042] Examples of layers in which the above-mentioned single or two or more kinds of metal oxides are laminated and / or mixed include laminated and / or mixed combinations of metal oxides such as titanium oxide / zinc oxide, titanium oxide / magnesium oxide, titanium oxide / zirconium oxide, titanium oxide / aluminum oxide, titanium oxide / hafnium oxide, titanium oxide / silicon oxide, zinc oxide / magnesium oxide, zinc oxide / zirconium oxide, zinc oxide / hafnium oxide, zinc oxide / silicon oxide, and calcium oxide / aluminum oxide, and laminated and / or mixed combinations of three kinds of metal oxides such as titanium oxide / zinc oxide / magnesium oxide, titanium oxide / zinc oxide / zirconium oxide, titanium oxide / zinc oxide / aluminum oxide, titanium oxide / zinc oxide / hafnium oxide, titanium oxide / zinc oxide / silicon oxide, and indium oxide / gallium oxide / zinc oxide. Among these, IGZO, an oxide semiconductor that exhibits good characteristics as a special composition, and 12CaO·7Al2O3, an electride, are also included. The first metal oxide layer can be called an electron injection layer and also an electrode (cathode). In the present invention, those with a sheet resistance lower than 100 Ω / □ are classified as conductors, and those with a sheet resistance higher than 100 Ω / □ are classified as semiconductors or insulators. Therefore, thin films of ITO (tin-doped indium oxide), ATO (antimony-doped indium oxide), IZO (indium-doped zinc oxide), AZO (aluminum-doped zinc oxide), FTO (fluorine-doped indium oxide), etc., which are known as transparent electrodes, are highly conductive and do not fall into the category of semiconductors or insulators, and therefore do not correspond to one layer constituting the first metal oxide layer.
[0043] Furthermore, the first metal oxide layer may be a laminate of a metal oxide layer and a layer of a simple metal, so long as it contains a metal oxide layer. The elements constituting the metal oxide are as described above. Examples of metals that can be used for the layer of a simple metal include silver and palladium, and one or more of these can be used.
[0044] When the first metal oxide layer is a laminate of a metal oxide layer and a layer of a simple metal, it is preferable that the metal oxide layer and the layer of the simple metal are alternately laminated. In this case, the number of metal oxide layers and the layer of the simple metal is preferably two metal oxide layers and one simple metal layer. In other words, a structure in which one simple metal layer is sandwiched between two metal oxide layers is preferable.
[0045] The metal oxide forming the second metal oxide layer is not particularly limited, and one or more of vanadium oxide (VO), molybdenum oxide (MoO), tungsten oxide (WO), ruthenium oxide (RuO) and the like can be used. Among these, vanadium oxide or molybdenum oxide is preferable as the main component. When the second metal oxide layer is composed of vanadium oxide or molybdenum oxide as the main component, the second metal oxide layer has a better function as a hole injection layer that injects holes from the anode and transports them to the light-emitting layer or the hole transport layer. In addition, vanadium oxide or molybdenum oxide has a high hole transport property by itself, and therefore has the advantage of being able to suitably prevent the efficiency of hole injection from the anode to the light-emitting layer or the hole transport layer from decreasing. More preferably, it is composed of vanadium oxide and / or molybdenum oxide.
[0046] The average thickness of the first metal oxide layer is permissible from about 1 nm to several μm, but from the viewpoint of obtaining an organic electroluminescent device that can be driven at a low voltage, it is preferably 1 to 1000 nm, and more preferably 2 to 100 nm. The average thickness of the second metal oxide layer is not particularly limited, but is preferably 1 to 1000 nm, and more preferably 5 to 50 nm. The average thickness of the first metal oxide layer can be measured by a stylus step gauge or spectroscopic ellipsometry. The average thickness of the second metal oxide layer can be measured as it is deposited using a quartz crystal thickness gauge.
[0047] In the organic electroluminescent device of the present invention, the anode and cathode can be appropriately made of known conductive materials, but it is preferable that at least one of them is transparent for light extraction. Examples of known transparent conductive materials include ITO (tin-doped indium oxide), ATO (antimony-doped indium oxide), IZO (indium-doped zinc oxide), AZO (aluminum-doped zinc oxide), and FTO (fluorine-doped indium oxide). Examples of opaque conductive materials include calcium, magnesium, aluminum, tin, indium, copper, silver, gold, platinum, and alloys thereof. Of these, ITO, IZO, and FTO are preferable for the cathode. Of these, Au, Ag and Al are preferable for the anode. As described above, since metals generally used for anodes can be used for the cathode and anode, it is easy to realize the case where light is extracted from the upper electrode (top emission structure), and various electrodes can be selected and used for each electrode. For example, Al can be used for the lower electrode and ITO for the upper electrode.
[0048] The average thickness of the cathode is not particularly limited, but is preferably 10 to 500 nm, and more preferably 100 to 200 nm. The average thickness of the cathode can be measured by a stylus step gauge or spectroscopic ellipsometry. The average thickness of the anode is not particularly limited, but is preferably 10 to 1000 nm. More preferably, it is 30 to 150 nm. Even when an opaque material is used, the anode can be used as a top emission type or transparent type anode by setting the average thickness to, for example, about 10 to 30 nm. The average thickness of the anode can be measured during deposition using a quartz crystal thickness gauge.
[0049] In the organic electroluminescence device of the present invention, the method of forming the coating layer of the organic material and / or inorganic material formed adjacent to the substrate and the layer formed from other organic compounds is not particularly limited, and various methods can be appropriately used according to the characteristics of the material. When the solution can be applied, the film can be formed by various application methods such as spin coating, casting, microgravure coating, gravure coating, bar coating, roll coating, wire bar coating, slit coating, dip coating, spray coating, screen printing, flexographic printing, offset printing, and inkjet printing. Among these, the spin coating and slit coating methods are preferred because the film thickness is easier to control. When no coating is performed or the solvent solubility is low, suitable examples include vacuum deposition and ESDUS (Evaporative Spray Deposition from Ultra-dilute Solution) methods. These methods can also be used when forming a coating layer of an organic material and / or an inorganic material having a thickness of 210 nm to 30 μm on a substrate.
[0050] When the layer formed from the organic compound or the coating layer of the organic material and / or inorganic material is formed by applying a solution or dispersion of the material, examples of the solvent used to prepare the solution or dispersion include inorganic solvents such as nitric acid, sulfuric acid, ammonia, hydrogen peroxide, water, carbon disulfide, carbon tetrachloride, and ethylene carbonate; ketone-based solvents such as methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), and cyclohexanone; alcohol-based solvents such as methanol, ethanol, isopropanol, ethylene glycol, diethylene glycol (DEG), and glycerin; diethyl ether, diisopropyl ether, 1,2-dimethoxyethane (DME), 1,4-dioxane, tetrahydrofuran (THF), tetrahydropyran (THP), anisole, diethylene glycol dimethyl ether (diglyme), diethylene glycol ethyl ether (carbito), and the like. Examples of the organic solvent include ether-based solvents such as hexane, pentane, heptane, and cyclohexane; cellosolve-based solvents such as methyl cellosolve, ethyl cellosolve, and phenyl cellosolve; aliphatic hydrocarbon-based solvents such as hexane, pentane, heptane, and cyclohexane; aromatic hydrocarbon-based solvents such as toluene, xylene, and benzene; aromatic heterocyclic compound-based solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, and methylpyrrolidone; amide-based solvents such as N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMA); halogen compound-based solvents such as chlorobenzene, dichloromethane, chloroform, and 1,2-dichloroethane; ester-based solvents such as ethyl acetate, methyl acetate, and ethyl formate; sulfur compound-based solvents such as dimethyl sulfoxide (DMSO) and sulfolane; nitrile-based solvents such as acetonitrile, propionitrile, and acrylonitrile; and organic acid-based solvents such as formic acid, acetic acid, trichloroacetic acid, and trifluoroacetic acid, or mixed solvents containing these. Among these, non-polar solvents are suitable as the solvent, and examples thereof include aromatic hydrocarbon solvents such as xylene, toluene, cyclohexylbenzene, dihydrobenzofuran, trimethylbenzene, and tetramethylbenzene; aromatic heterocyclic compound solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, and methylpyrrolidone; and aliphatic hydrocarbon solvents such as hexane, pentane, heptane, and cyclohexane. These can be used alone or in combination.
[0051] The cathode, anode, and oxide layer can be formed by sputtering, vacuum deposition, sol-gel, spray pyrolysis (SPD), atomic layer deposition (ALD), vapor phase deposition, liquid phase deposition, and the like. Metal foil bonding can also be used to form the anode and cathode. These methods are preferably selected according to the characteristics of the material of each layer, and the fabrication method may be different for each layer. Among these, it is more preferable to form the second metal oxide layer using a vapor phase deposition method. According to the vapor phase deposition method, the organic compound layer can be formed cleanly and in good contact with the anode without destroying the surface, and as a result, the effect of having the second metal oxide layer as described above becomes more remarkable.
[0052] For the purpose of further improving the properties of the organic electroluminescent device, for example, a hole blocking layer, an electron blocking layer, etc. may be provided as necessary. As materials for forming these layers, materials usually used for forming these layers are used, and the layers can be formed by methods usually used for forming these layers.
[0053] In addition, after forming the last electrode of the laminated structure, a passivation layer for protecting the surface may be formed thereon. The material of the passivation layer may be any material that is usually used to form these layers. For example, the material of the hole transport layer and / or the material of the metal oxide layer described above may be used, but is not limited to this as long as the combination can maintain insulation.
[0054] The average thickness of the passivation layer is not particularly limited, but is preferably 20 to 300 nm, and more preferably 50 to 200 nm. The average thickness of the passivation layer can be measured as it is deposited using a quartz crystal thickness gauge.
[0055] As the substrate of the organic electroluminescent device of the present invention, a substrate having a barrier layer formed thereon for sealing can be used. Examples of materials for the substrate include resin materials such as polyethylene terephthalate, polyethylene naphthalate, polypropylene, cycloolefin polymer, polyamide, polyethersulfone, polymethyl methacrylate, polycarbonate, and polyarylate. Examples of materials for forming a barrier layer on a substrate include silicon oxide, zinc oxide, titanium oxide, silicon nitride, aluminum oxide, polysilazane, and parylene.
[0056] The average thickness of the substrate is preferably 10 to 150 μm, and more preferably 10 to 50 μm. The average thickness of the substrate can be measured by digital calipers.
[0057] The organic electroluminescent device may further have a sealing layer on the passivation layer. The material for forming the sealing layer may be the same as the material for the substrate, and the thickness of the sealing layer is preferably the same as the thickness of the substrate.
[0058] When sealing the organic electroluminescence element of the present invention, a conventional method can be appropriately used as the sealing step. For example, a method of bonding a sealing container in an inert gas, a method of forming a sealing film directly on the organic electroluminescence element, etc. can be mentioned. In addition to these, a method of sealing a moisture absorbing material may be used in combination. The organic electroluminescent device having the above-mentioned inverted structure does not require strict sealing as compared with the organic electroluminescent device having the forward structure, but may be sealed if necessary.
[0059] The organic electroluminescent device may be of a top emission type in which light is extracted from the side opposite to the side where the substrate is located, or of a bottom emission type in which light is extracted from the side where the substrate is located.
[0060] The organic electroluminescent device of the present invention is a device having improved atmospheric stability by having a coating layer of an organic material and / or an inorganic material of a predetermined thickness between a substrate and a lower electrode, and can be suitably used as a material for display devices and lighting devices. Such a display device or lighting device formed using the organic electroluminescent device of the present invention also constitutes the present invention. EXAMPLES
[0061] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by mass".
[0062] 1. Preparation of organic electroluminescent device Example 1 An organic electroluminescent device 1 having the structure shown in FIG. 1 was manufactured by the method described below. [Process 1] A 25 μm-thick PET film with a barrier layer purchased from Oike Kogyo Co., Ltd. was used as the substrate 1, and SU-8 manufactured by Nippon Kayaku Co., Ltd. was applied onto the film by spin coating and baked on a hot plate heated to 130° C. to form a coating layer 2 with a thickness of 250 nm. [Process 2] The substrate 1 on which the coating layer was formed was set in a sputtering device, and a zinc oxide (ZnO) layer with an average thickness of 20 nm was formed on the coating layer by sputtering using zinc metal as a target, oxygen as a reactive gas, and argon as a carrier gas. The substrate was then set in a vacuum deposition device, and a silver layer with an average thickness of 8 nm was formed. The substrate was then set in the sputtering device again, and a zinc oxide layer with an average thickness of 2 nm was formed. The substrate 1 was then moved to the atmosphere, and annealed on a hot plate at 100°C for 30 minutes. As a result, an oxide layer 3, a transparent electrode 4, and an oxide layer 5 were formed on the coating layer 2. [Process 3] Next, polyethyleneimine manufactured by Nippon Shokubai Co., Ltd. was applied onto the oxide layer 5 by spin coating to form an electron injection layer 6. The average thickness of the electron injection layer 6 was 2 nm. [Step 4] Next, the substrate 1 on which each layer up to the electron injection layer 6 had been formed was fixed to a substrate holder of a vacuum deposition apparatus. In addition, KHLHS-04, KHLDR-03, and N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD) represented by the following formula (1), all of which were purchased from Chemipro Chemicals, were placed in alumina crucibles and set as deposition sources. The interior of the vacuum deposition apparatus was then filled with approximately 1×10 -5 The pressure was reduced to 20 Pa, and KHLHS-04 was evaporated to 10 nm to form an electron transport layer 7. Next, KHLHS-04 and α-NPD were co-evaporated to 15 nm using KHLDR-03 as an emitting dopant to form an emitting layer 8. Next, α-NPD was evaporated to 40 nm to form a hole transport layer 9. Furthermore, molybdenum trioxide MoO3 was evaporated throughout the vacuum to form a hole injection layer 10 with a thickness of 10 nm. [Step 5] Next, aluminum (anode 11) was evaporated onto the substrate 1 on which the hole injection layer 10 had been formed, to a film thickness of 70 nm. [Step 6] Next, α-NPD was evaporated to a thickness of 100 nm onto the substrate 1 on which the anode 11 had been formed, and then zinc oxide was deposited to a thickness of 20 nm using a sputtering device, thereby obtaining a passivation layer 12. [Step 7] Next, the substrate 1 on which the passivation layer 12 had been formed was transported to a glove box, and TB1655 manufactured by ThreeBond and a 25 μm-thick PET film with a barrier layer purchased from Oike Kogyo Co., Ltd. were laminated onto the substrate 1, and annealed for 1 hour on a hot plate heated to 90° C. to form a sealing layer 13, thereby obtaining "Element 1," an embodiment of the present invention. The thickness of the obtained element 1 was measured by a Mitutoyo Corporation Digimatic Indicator, ID-C112AB, and the total film thickness was 72 μm.
[0063] Example 2 An "element 2" of the present invention was obtained in the same manner as in Example 1, except that in [Step 1] of Example 1, the thickness of the coating layer 2 formed on the PET film with a barrier layer was changed to 27 μm.
[0064] Example 3 In [Step 1] of Example 1, the coating layer 2 formed on the PET film with a barrier layer was changed from SU-8 manufactured by Nippon Kayaku Co., Ltd. to a mixture of zinc acetate hydrate, monoethanolamine, and 2-methoxyethanol purchased from Sigma-Aldrich, and the thickness was changed to 220 nm, but the same procedure as in Example 1 was repeated to obtain "Element 3," an example of the present invention.
[0065] Comparative Example 1 A "comparative element 1", which is a comparative example of the present invention, was obtained in the same manner as in Example 1, except that in [Step 1] of Example 1, the thickness of the coating layer 2 formed on the PET film with a barrier layer was changed to 35 μm.
[0066] Comparative Example 2 A "comparative element 2", which is a comparative example of the present invention, was obtained in the same manner as in Example 1, except that in [Step 1] of Example 1, the thickness of the coating layer 2 formed on the PET film with a barrier layer was changed to 150 nm.
[0067] 2. Observation of light emission from organic electroluminescent devices For the elements 1 to 3 and comparative elements 1 and 2 produced in Examples 1 to 3 and Comparative Examples 1 and 2, a voltage of -3 V was applied to the elements and the leakage current was measured using a Keithley 2400 Source Meter. The elements were then left for 100 hours in an environment at a temperature of 85°C and a relative humidity of 85%, after which the EL emission was photographed. The results for elements 1 to 3 and comparative elements 1 and 2 are shown in Table 1 and Figures 2 to 6, respectively.
[0068] [Table 1]
[0069] As shown above, it is clear that elements 1, 2, and 3 have low leakage current, and that foreign objects and defects on substrate 1 are covered and flattened. Furthermore, even when stored in an environment with a temperature of 85°C and a relative humidity of 85%, there is no deterioration in the light-emitting surface, indicating high atmospheric stability. On the other hand, comparison element 1 has a low leakage current and the substrate is flattened, but because coating layer 2 is too thick, its atmospheric stability is low. It is clear that comparison element 2 has a large leakage current and also has low atmospheric stability. From these results, it was confirmed that by forming a coating layer of a predetermined thickness adjacent to a substrate, an organic electroluminescent device with high atmospheric stability can be obtained.
Claims
1. An organic electroluminescence device having a structure in which one of an anode and a cathode is a lower electrode and the other is an upper electrode, and a plurality of layers are laminated between the lower electrode and the upper electrode, The organic electroluminescent device is characterized by having, in this order, a substrate, a coating layer of an organic material and / or an inorganic material having a thickness of 210 nm to 30 μm formed adjacent to the substrate, a lower electrode, an organic compound layer, and an upper electrode.
2. 2. The organic electroluminescent device according to claim 1, wherein the coating layer is a coating layer of an organic material.
3. The organic electroluminescent device according to claim 2 , wherein the organic material has a glass transition temperature higher than that of the substrate.
4. 2. The organic electroluminescent device according to claim 1, wherein the lower electrode is a cathode and the upper electrode is an anode.
5. 2. The organic electroluminescent device according to claim 1, further comprising an oxide layer between the coating layer and the lower electrode.
6. A display device comprising the organic electroluminescent device according to any one of claims 1 to 5.
7. A lighting device comprising the organic electroluminescent element according to any one of claims 1 to 5.